Evaluating dental implant stability using three devices Osstell®, Periotest®, and AnyCheck®: a clinical study - Dhahi Alamin Y.; Bede Salwan Y. (Journal of Oral Medicine and Oral Surgery)
Introduction: Implant stability is usually measured with resonance frequency analysis (RFA) and damping capacity assessment (DCA). This study aimed to measure primary and secondary stabilities using 3 devices that are based on these methods, namely; RFA (Osstell®) and DCA (Periotest® and AnyCheck®) to assess the correlations of the measurements obtained by these devices and the correlations between implant stability and insertion torque. Material and Methods: This observational prospective study included 35 dental implants. The implant stability was measured using the 3 devices. Mann–Whitney U test and unpaired t-test assessed the relationship between implant stability and insertion torque, while the Spearman and Pearson correlations measured the correlation between readings collected via the 3 devices for the primary and secondary stabilities. Results: For the primary stability, there was a strong positive correlation between Osstell® and AnyCheck® and moderate negative correlations between Periotest® and both Osstell® and AnyCheck®. While for the secondary stability, strong correlations with similar patterns were observed among the 3 devices. The stability measurements showed significant relationships with the insertion torque. Conclusions: The 3 devices are reliable in measuring implant stability; also, high insertion torque can lead to improved implant stabilities (primary and secondary).